A literature review: Security Aspects in the Implementation of Electronic Medical Records in Hospitals - Piping Asgiani; Chriswardani Suryawati; Farid Agushybana (MEDIA ILMU KESEHATAN, 2021)
Backgrounds: Electronic Medical Records have complete and integrated patient health data, and are up to date because RME combines clinical and genomic data, this poses a great risk to data disclosure The priority of privacy is data security (security) so that data will not leak to other parties. That way cyber attacks can be suppressed by increasing cybersecurity, namely conducting regular evaluation and testing of security levels.Objectives: To determine the security technique that maintains privacy of electronic medical records.Methods: This type of research uses a literature review methodResults: Data security techniques are determined from each type of health service. Data security techniques that can be applied are cryptographic methods, firewalls, access control, and other security techniques. This method has proven to be a very promising and successful technique for safeguarding the privacy and security of RMEConclusion: Patient medical records or medical records are very private and sensitive because they store all data about complaints, diagnoses, disease histories, actions, and treatments about patients, so the information contained therein must be kept confidential. As well as the hospital as a medical record manager is required to apply for patient privacy data security techniques.